Alasan Menikah Usia Dini berdasarkan Sikap Remaja di Wilayah Kecamatan Onembute Kabupaten Konawe - Jayanti, Andi; Tasnim, Tasnim; Fatmawati, Fatmawati (Jurnal Gizi Ilmiah, 2018)
Early marriage not only robs the future of teenagers, but also has a negative impact on health and has an impact on dropping out of school, where 85 percent of girls in Indonesia end their education after they get married. Southeast Sulawesi itself is in the top 10, a province that has the highest number of female adolescent marriages aged (15-19) years. This study aims to determine how early marriage occurs in Oneembute District, Konawe Regency. This type of research is a qualitative research with a phenomenological approach. In this study, adopting the theory of reasoned action as the basis for behavioral theory. The informants in this study consisted of 4 key informants and 9 ordinary informants. the technique of determining the informants used snowball and purposive sampling techniques. To collect data/information using observation techniques, in-depth interviews and documentation. The results showed that the attitude of the informant regarding the age of early marriage was neither a threat nor did it raise awareness of the informant after marriage. This was influenced by the experience of the informant who married early, this is a result of the understanding and knowledge of the informant is still very limited.